UNIVERSITY AS A KEY ELEMENT OF THE CORE OF AN INNOVATIVE ECOSYSTEM - S. Poltotykhina (Вестник Северо-Кавказского федерального университета, 2022)
In the article emphasizes the needfor the formation and development of a regional innovation system in order to effectively conduct the innovation process, disseminate knowledge and innovations. The process of formation of an innovation ecosystem, the key link of which is the university, is described. The importance of the university as a key element of the core of the innovation ecosystem is substantiated. The essence of the innovation ecosystem is revealed through the prism of the concepts of «triple helix» and «five spirals». The properties of the core of the innovation ecosystem are discussed. The role of entrepreneurial and transitive universities in the functioning of the innovation ecosystem is substantiated. The acceleration of the practical implementation of new knowledge in the context of modern economic development is emphasized due to the primary role of universities in the innovation process.